Ductal Carcinoma In Situ and Microinvasive/Borderline Breast Cancer - Newman, Lisa A.; Bensenhaver, Jessica M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This volume reviews the evolution of information regarding the epidemiology of DCIS and its modes of detection, as well as treatment options as a function of both clinical trial data and ongoing investigational therapeutic prospects. Several of the challenging and clinically-relevant scenarios of DCIS that appear in daily practice is discussed, including the difficulties of distinguishing “true” DCIS from borderline patterns of other breast diseases and the therapeutic implications of differentiating these various diagnoses. Particular attention is paid to pathologic evaluation of DCIS, including histologic patterns and the importance of margin evaluation/margin control. The text also explores the data regarding DCIS in medical research in hereditary susceptibility for breast cancer and race/ethnicity-associated disparities in breast cancer. Written by experts in the field, Ductal Carcinoma In Situ and Microinvasive/Borderline Breast Cancer is a comprehensive, state-of-the art review of the field, and serves as a valuable resource for clinicians, surgeons and researchers with an interest in breast cancer.
Epidemiology of Ductal Carcinoma In Situ -- Role of Screening Mammography in Early Detection/Outcome from Breast Cancer -- Imaging DCIS: Digital/Film Screening Mammography, Tomosynthesis, MRI, Ultrasonography -- Pathology of Ductal Carcinoma In Situ: Features and Diagnostic Challenges -- Molecular Markers in DCIS -- History of Ductal Carcinoma In Situ Management Based Upon Data from Prospective, Randomized Clinical Trials -- Extent and Role of Margin Control for DCIS Managed by Breast-Conserving Surgery -- Ductal Carcinoma In Situ Treated With Breast Conserving Surgery Alone -- DCIS Managed with BCS: Whole-Breast XRT vs. Partial Breast XRT -- Anti-HER2/neu Therapy in DCIS -- Role of Genetic Profiling and Recurrence Scores in Treatment Planning for DCIS -- DCIS and Sentinel Lymph Node Biopsy -- Role of Postmastectomy Radiation for DCIS -- Monitoring and Surveillance Following DCIS Treatment -- DCIS and Hereditary Susceptibility for Breast Cancer -- Introduction, Evolution and Application of the Van Nuys Prognostic Index in DCIS -- Disparities in DCIS Detection and Outcomes Related to Race/Ethnicity.
Keywords: Surgery; Surgical oncology; Gynecology .; Surgery; Surgical Oncology; Gynecology